Wild Cinchona (Neolamarckia cadamba) Bioactivities of a Medicinal Plant of Bangladesh (Bangladesh Pharmaceutical Journal, 2016)
The methanol extract of bark of Neolamarckia cadamba (Roxb.) and its organic and aqueous soluble partitionates were subjected to assays for antioxidant, cytotoxic, thrombolytic, membrane stabilizing, antimicrobial and analgesic activities. In the DPPH free radical scavenging assay, the pet ether and carbon tetra chloride soluble partitionate of the methanolic extract demonstrated the highest free radical scavenging activity with IC50 values of 60.46 ?g/ml and 78.58 ?g/ml, respectively. On the other hand, the carbon tetrachloride and pet ether soluble fractions displayed the potential lethality to brine shrimps, having LC50 of 7.24 and 7.89 ?g/ml, as compared to standard vincristine sulphate (LC50 value of 0.45 ?g/ml). During assay for thrombolytic property, the carbon tetrachloride and aqueous soluble materials revealed 66.36 % and 64.25 % clot lysis of human blood, respectively. In the membrane stabilizing assay, the carbon tetrachloride soluble fraction inhibited 86.79 % haemolysis of human RBCs in hypotonic solution-induced condition, while the aqueous soluble partitionate inhibited 92.39 % haemolysis of RBCs in the heat-induced condition. The crude methanolic extract of bark of N. cadamba showed significant central and peripheral analgesic activity at both 200 and 400 mg/kg body weight, whereas its chloroform soluble fraction mildly inhibited the growth of test microorganisms. Therefore, our studies suggest that wild cinchona should be subjected to extensive phytopharmacological investigation.Bangladesh Pharmaceutical Journal 19(1): 32-36, 2016